The Influence of Student Team-achievement Division (STAD) in Developing Students’ Speaking Skill - Rahmat Firnanda; Sofyan A. Gani; Iskandar Abdul Samad (English Education Journal, 2019)
The research was implemented to find out the effectiveness of students team achievement division (STAD) as a part of cooperative learning in teaching speaking to improve the students’ speaking skill and also to know the students’ responses toward the implementation of STAD in teaching speaking at XI IA 2 class of SMAN 1 Lhoong, Aceh Besar. The population of the study was the eleventh graders of SMAN 01 Lhoong, Aceh Besar. The number of the samples was 40 students consisting of 20 students from the class XI IA 2 as the experimental group, and 20 students chosen from the class XI IS 2 as the control group. The data of this research were collected by giving tests; (pretest, posttest), and questionnaire. The data collections were analyzed by using SPSS 17. The percentage formula was used to analyze the students’ perceptions toward the implementation of STAD in the experimental group. The result shows that the mean score of experimental group was 70.95. Meanwhile the control group was 68.70. Moreover, the significant value of both the experimental and control groups in the post-test was 0.04 which is lower than α=0.05. It means that Ha was accepted and H0 was rejected and it can be concluded that the use of STAD in teaching speaking skill enhanced the students’ speaking skill, compared to the teaching speaking in conventional method. Meanwhile, the result of questionnaires shows that STAD could enhance the students’ confidence in learning speaking skill.